INTEGRASI IMTAQ DAN IPTEK DALAM PEMBELAJARAN DI LINGKUNGAN LEMBAGA PENDIDIKAN ISLAM SMP PLUS AL-KAUTSAR MALANG - Soelaiman, Soelaiman (J-PAI: Jurnal Pendidikan Agama Islam, 2016)
Currently in this era of globalization, there is a negative influence of the electronic media and print media on people's lives. Islamic community life that sees religion merely as a ritual activity is not conducive to improving the IMTAQ. In addition, there are many partially learners (especially in big cities) misbehaves (perkelaian students, brawling, drug abuse, sexual perversion, and other juvenile delinquency). The problems above, has not answered what the objectives of national education in an effort to increase the faith and devotion in order to achieve the life of the nation. Thus, it is not wrong if we look at the integration of science in education IMTAQ and this is a major issue that must be executed. IMTAQ integration efforts and science and technology in learning can be done in two reviews that environment-Islamic and Islamic resources.Â Keywords: Integration, IMTAQ, IPTEK